Modern Approach to Comprehensive Rehabilitation of Patients with Face Defects (Texas Journal of Medical Science, 2023)
The article describes the issues of surgical treatment and rehabilitation of patients diagnosed with face-jaw deformity. Treatment and rehabilitation of patients with acquired maxillofacial defects (OMD) is one of the most urgent medical and social problems of modern dentistry. Wide-scale and integrated rehabilitation measures are important in the specialized dental care system, because OC is often accompanied by serious aesthetic and functional disorders, which, in turn, limit the patient's life activities, cause his inability to adapt to the social environment, and cause deep socio-psychological problems. causes problems.